A ceramic splitting knife and surface roughening treatment method thereof
Through the combination of modified alumina powder and nanomaterials and multi-energy field treatment, the hardness and bending strength of the ceramic chopper are improved, and the problems of insufficient hardness and insufficient surface roughness of the ceramic chopper are solved, achieving more efficient Welding performance and service life.
Patent Information
- Application Number
- CN202410992851.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-24
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-07-24
AI Technical Summary
The existing ceramic choppers are insufficient in the welding process, have large porosity of the material, and low bending strength. It is difficult for existing heat treatment methods to obtain suitable surface roughness, which affects service life and quality of the welding line.
The ceramic splitting knife is prepared by ball milling, drying, sieving, glue discharge and sintering treatment, and multi-energy field assisted treatment is used to prepare the ceramic splitting knife. Surface coarsing, including the use of ultrasonic waves, microwaves and magnetic fields.
It improves the hardness, fracture toughness and bending strength of the ceramic chopper, obtains appropriate surface roughness, extends service life and improves the reliability of the welding points, and is suitable for different application environments and packaging methods.
Smart Images

Figure CN118545987B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of semiconductor chip packaging, and in particular to a ceramic splitting knife and a surface roughening treatment method thereof. Background Art
[0002] Ceramic splitters are axially symmetrical ceramic tools with vertical holes. They are precision microstructure ceramic parts and are wire bonding tools used in the wire bonding process in the field of microelectronics processing. They play an extremely important role in packaging technology. Ceramic splitters are widely used in semiconductor IC packaging and LED packaging due to their extremely high hardness, insulation, corrosion resistance, high temperature resistance, high surface finish, high dimensional accuracy, and long service life. The widespread use of ceramic splitters has enabled the modern microelectronics industry to further develop in the direction of large-scale integration, miniaturization, high efficiency, and high reliability.
[0003] The existing ceramic splitting knives for semiconductor packaging are generally made of ZTA material zirconium oxide toughened alumina ceramics. Zirconium oxide is doped into alumina to make the microstructure of the material uniform and dense. The splitting knives made of this material have good chemical corrosion resistance and wear resistance. However, the ceramic splitting knives made of ZTA material have relatively low hardness and high material porosity. When copper is used as the welding wire, due to the high hardness of copper, a large ultrasonic energy is required during welding. During welding, the end face of the splitting knives will be subjected to large shear stress, and the crystal particles are easy to fall off, which increases the degree of wear on the end face of the splitting knives and shortens its service life. It can be seen that it is necessary to further improve the ceramic splitting knives from the perspective of component formulation.
[0004] When using a ceramic splitter, its working surface (i.e., T-surface) is required to have different roughness depending on the application scenario. Roughness has a great influence on the service life of the splitter and the quality of the welding line. Most of the existing technologies roughen the surface of the ceramic splitter through direct heat treatment methods, and control the roughness of the working surface of the ceramic splitter by the temperature of the heat treatment. However, it is difficult to obtain a relatively rough surface through direct heat treatment processes, and the range of temperature-adjusted surface roughness is limited. This is mainly because the grains on the surface of the ceramic splitter become clear and convex in order to reduce the surface energy under high temperature. However, due to the surface tension of the material, the degree of grain protrusion is limited. If the temperature is higher than the firing temperature of the ceramic splitter, the grain boundaries migrate, resulting in grain growth, which will affect the performance of the product. It can be seen that it is necessary to seek a more suitable surface roughening treatment method for ceramic splitters.
[0005] In order to solve the above problems, the Chinese invention patent with the authorization announcement number CN106995308B discloses a ceramic splitting knife material, which contains the following components in weight percentage: 65-92.99% of base ceramic, 0.1-30% of auxiliary ceramic, and 0.1-30% of additives; wherein the base ceramic is at least one of aluminum oxide and zirconium oxide; the auxiliary ceramic is at least one of zirconium oxide, chromium oxide, erbium oxide, niobium pentoxide, zinc oxide, iron oxide, titanium oxide, calcium oxide, magnesium oxide, silicon carbide, strontium oxide, barium oxide, silicon nitride, and tungsten carbide. The invention also discloses a ceramic splitting knife prepared using the above ceramic splitting knife material. The ceramic splitting knife material prepared by the invention has the properties of high hardness, large density, small average particle size, good toughness, etc. after being ceramicized. The crystal particles are not easy to fall off during use, and have excellent wear resistance. However, the bending strength of the material needs to be further improved. In order to meet different application environments and packaging methods, the ceramic splitting knife made of the material also needs to be combined with a suitable surface roughening treatment method. Summary of the invention
[0006] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a ceramic splitting knife with sufficient hardness, good fracture toughness and bending strength, high density, suitable surface roughness, and capable of meeting different application environments and packaging methods, and a surface roughening treatment method thereof.
[0007] To achieve the above object, the technical solution adopted by the present invention is: a ceramic splitting knife is made of the following components by weight: 70-90 parts of modified alumina powder, 3-5 parts of nano-boron fiber, 3-5 parts of auxiliary nano-particles, and 3-5 parts of binder; the modified alumina powder is rare earth / Zr / W / M / N co-modified alumina powder; the M is at least one of Nb, Ni, Ga, Cr, and Co; the N is B, Si, and Te mixed in a molar ratio of 1:(0.8-1.2):0.2.
[0008] Preferably, the preparation method of the modified alumina powder comprises the following steps: placing an aluminum source, a rare earth source, a zirconium source, a tungsten source, an M source, a N source and citric acid in distilled water and stirring evenly, spray drying and calcining in air at 350-450°C for 2-4 hours, then calcining in air at 700-900°C for 8-10 hours, and after natural cooling, grinding the product through a 300-500 mesh sieve to obtain modified alumina powder.
[0009] Preferably, the molar ratio of the aluminum source, rare earth source, zirconium source, tungsten source, M source, N source, citric acid and distilled water is 1:0.08:(0.08-0.15):(0.03-0.05):(0.05-0.08):0.001:1:(6-10).
[0010] Preferably, the aluminum source is aluminum nitrate; and the rare earth source is at least one of yttrium nitrate, lanthanum nitrate and praseodymium nitrate.
[0011] Preferably, the zirconium source is zirconium acetate; the tungsten source is tungsten nitrate; the M source is nitrate of M; and the N source includes ammonium borate, ammonium silicate, and ammonium tellurate.
[0012] Preferably, the average diameter of the nano-boron fiber is 300-500 nm, and the aspect ratio is (15-25):1.
[0013] Preferably, the auxiliary nanoparticles are a mixture of nano-silicon boride, nano-hafnium nitride, nano-tantalum silicide and nano-titanium carbide in a mass ratio of 1:(0.8-1.2):(1-2):0.8.
[0014] Preferably, the particle size of the auxiliary nanoparticles is 10-90 nm.
[0015] Preferably, the binder comprises the following components in parts by weight: 4-6 parts of rosin-based hyperbranched epoxy resin, 1-3 parts of hydroxypropyl β-cyclodextrin, and 1-3 parts of (3,6-diaminoacridine-9-yl)boric acid.
[0016] Preferably, there is no special requirement for the source of the rosin-based hyperbranched epoxy resin. In one embodiment of the present invention, the rosin-based hyperbranched epoxy resin is prepared according to the method of Example 1 of the Chinese invention patent with authorization announcement number CN106519188B.
[0017] Another object of the present invention is to provide a method for preparing the ceramic splitting knife, comprising the following steps:
[0018] Step S1, mixing the components uniformly by weight to obtain a mixed material, and ball-milling the mixed material to obtain a uniform powder;
[0019] Step S2, drying, sieving, debinding and shaping the uniform powder obtained in step S1 in sequence to obtain a green body;
[0020] Step S3, sintering the green body to obtain a ceramic splitting knife.
[0021] Preferably, the drying in step S2 is carried out under vacuum, at a drying temperature of 80-90° C., and dried to constant weight.
[0022] Preferably, the sieving in step S2 is sieving through a 300-600 mesh sieve; the debinding is performed in a vacuum environment, the debinding temperature is 440-510° C., and the debinding time is 1-3 h.
[0023] Preferably, the sintering conditions in step S3 are: heating rate 3-8°C / min, sintering temperature 1430-1660°C, and holding time 4-8h.
[0024] Another object of the present invention is to provide a surface roughening treatment method of the ceramic splitting knife, comprising the following steps:
[0025] Step D1, the ceramic splitter is immersed in a mixed acid solution, using a multi-energy field assisted treatment for 15-25min;
[0026] Step D2, cleaning and drying the ceramic splitting knife processed in step D1 to obtain a roughened ceramic splitting knife product.
[0027] Preferably, the mixed acid in step D1 is a mixture of nitric acid solution and sulfuric acid solution in a volume ratio of 1:(0.8-1.2).
[0028] Preferably, the mass percentage concentration of the nitric acid solution is 25-55%, and the mass percentage concentration of the sulfuric acid solution is 45-85%.
[0029] Preferably, the multi-energy field includes ultrasound, microwave and magnetic field; the ultrasound frequency is 50-100kHz, and the power is 200-400W; the microwave frequency is 2.3-3.0GHz, and the power is 700-1400W; the magnetic field strength of the magnetic field is 8000-16000Gs.
[0030] Due to the application of the above technical solution, the present invention has the following beneficial effects:
[0031] (1) The preparation method and surface roughening treatment method of the ceramic splitter disclosed in the present invention have simple process, convenient operation and control, high preparation efficiency and finished product qualification rate, low energy consumption, low dependence on equipment, suitable for continuous large-scale production, and high promotion and application value. The use of multi-energy field auxiliary treatment in the surface roughening process can effectively improve the surface roughening effect and efficiency to meet the requirements of the surface roughness of the ceramic splitter in different application environments and packaging methods.
[0032] (2) The ceramic splitter disclosed in the present invention is made of the following components by weight: 70-90 parts of modified alumina powder, 3-5 parts of nano-boron fiber, 3-5 parts of auxiliary nanoparticles, and 3-5 parts of binder; the modified alumina powder is rare earth / Zr / W / M / N co-modified alumina powder; the M is at least one of Nb, Ni, Ga, Cr, and Co; the N is B, Si, and Te mixed in a molar ratio of 1:(0.8-1.2):0.2. Through the reasonable selection of different components and ingredients, and the mutual cooperation between the components, the ceramic splitter has sufficient hardness, good fracture toughness and bending strength, high density, and appropriate surface roughness, which can meet different application environments and packaging methods.
[0033] (3) The ceramic splitter disclosed in the present invention, the auxiliary nanoparticles are a mixture of nano-boron silicon, nano-hafnium nitride, nano-tantalum silicide, and nano-titanium carbide in a mass ratio of 1: (0.8-1.2): (1-2): 0.8; the binder includes the following components in parts by weight: 4-6 parts of rosin-based hyperbranched epoxy resin, 1-3 parts of hydroxypropyl β-cyclodextrin, and 1-3 parts of (3,6-diaminoacridine-9-yl) boric acid. By rationally selecting the binder composition and the auxiliary nanoparticle composition formula, the components can cooperate with each other well, giving the material advantages such as dense crystal phase, uniform and refined structure, good bonding quality, and high reliability of welding points.
[0034] (4) The ceramic splitting knife disclosed in the present invention can further improve the hardness, fracture toughness, bending strength and density of the ceramic splitting knife through the reasonable selection of various process parameters in the preparation process; the surface of the ceramic splitting knife is roughened by the mixed acid + multi-energy field auxiliary treatment method, which can improve the effect and efficiency of the surface roughening treatment. The surface roughness is appropriate and can be controlled by the treatment time and the mass percentage concentration of the acid to meet the requirements of the surface roughness of the ceramic splitting knife in different application environments and packaging methods. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is a microstructure diagram of the ceramic splitting knife according to Example 1 of the present invention. DETAILED DESCRIPTION
[0036] The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are only examples, and those skilled in the art may think of other obvious variations.
[0037] Embodiment 1, a ceramic splitting knife is made of the following components in parts by weight: 70 parts of modified alumina powder, 3 parts of nano-boron fiber, 3 parts of auxiliary nanoparticles, and 3 parts of a binder; the modified alumina powder is a rare earth / Zr / W / M / N co-modified alumina powder; the M is Nb; the N is a mixture of B, Si, and Te in a molar ratio of 1:(0.8-1.2):0.2.
[0038] The preparation method of the modified alumina powder comprises the following steps: placing an aluminum source, a rare earth source, a zirconium source, a tungsten source, an M source, a N source and citric acid in distilled water and stirring evenly, spray drying, calcining in air at 350°C for 2 hours, then calcining in air at 700°C for 8 hours, naturally cooling, grinding the product through a 300-mesh sieve, and obtaining the modified alumina powder; the molar ratio of the aluminum source, the rare earth source, the zirconium source, the tungsten source, the M source, the N source, the citric acid and the distilled water is 1:0.08:0.08:0.03:0.05:0.001:1:6; the aluminum source is aluminum nitrate; the rare earth source is yttrium nitrate; the zirconium source is zirconium acetate; the tungsten source is tungsten nitrate; the M source is a nitrate of M; and the N source comprises ammonium borate, ammonium silicate and ammonium tellurate.
[0039] The average diameter of the nano-boron fiber is 300nm, and the aspect ratio is 15:1; the auxiliary nanoparticles are a mixture of nano-boron silicon, nano-hafnium nitride, nano-tantalum silicide, and nano-titanium carbide in a mass ratio of 1:0.8:1:0.8; the particle size of the auxiliary nanoparticles is 10nm; the binder includes the following components in parts by weight: 4 parts of rosin-based hyperbranched epoxy resin, 1 part of hydroxypropyl β-cyclodextrin, and 1 part of (3,6-diaminoacridine-9-yl)boric acid; the rosin-based hyperbranched epoxy resin is made according to the method of Example 1 of the Chinese invention patent with authorization announcement number CN106519188B.
[0040] A method for preparing the ceramic splitting knife comprises the following steps:
[0041] Step S1, mixing the components uniformly by weight to obtain a mixed material, and ball-milling the mixed material to obtain a uniform powder;
[0042] Step S2, drying, sieving, debinding and shaping the uniform powder obtained in step S1 in sequence to obtain a green body;
[0043] Step S3, sintering the green body to obtain a ceramic splitting knife.
[0044] The drying in step S2 is carried out under vacuum, the drying temperature is 80°C, and the drying is carried out to constant weight; the screening in step S2 is through a 300-mesh sieve; the debinding is carried out under vacuum, the debinding temperature is 440°C, and the debinding time is 1h; the sintering treatment conditions in step S3 are: heating rate 3°C / min, sintering temperature 1430°C, and insulation time 4h.
[0045] A surface roughening treatment method of the ceramic splitting knife comprises the following steps:
[0046] Step D1, the ceramic splitter is immersed in a mixed acid solution, using a multi-energy field assisted treatment for 15min;
[0047] Step D2, cleaning and drying the ceramic splitting knife processed in step D1 to obtain a roughened ceramic splitting knife product.
[0048] The mixed acid in step D1 is a mixture of nitric acid solution and sulfuric acid solution in a volume ratio of 1:0.8; the mass percentage concentration of the nitric acid solution is 25%, and the mass percentage concentration of the sulfuric acid solution is 45%; the multi-energy field includes ultrasound, microwave and magnetic field; the ultrasound frequency is 50kHz and the power is 200W; the microwave frequency is 2.3GHz and the power is 700W; the magnetic field strength of the magnetic field is 8000Gs.
[0049] from Figure 1 It can be seen that the ceramic splitter has dense crystal phase and uniform structure.
[0050] Example 2, a ceramic splitting knife, is made of the following components in parts by weight: 75 parts of modified alumina powder, 3.5 parts of nano-boron fiber, 3.5 parts of auxiliary nanoparticles, and 3.5 parts of a binder; the modified alumina powder is a rare earth / Zr / W / M / N co-modified alumina powder; the M is Ni; the N is a mixture of B, Si, and Te in a molar ratio of 1:0.9:0.2.
[0051] The preparation method of the modified alumina powder comprises the following steps: placing an aluminum source, a rare earth source, a zirconium source, a tungsten source, an M source, an N source and citric acid in distilled water and stirring evenly, spray drying and calcining in air at 380°C for 2.5 hours, then calcining in air at 750°C for 8.5 hours, naturally cooling and grinding the product through a 350-mesh sieve to obtain a modified alumina powder; the molar ratio of the aluminum source, the rare earth source, the zirconium source, the tungsten source, the M source, the N source, the citric acid and the distilled water is 1:0.08:0.1:0.035:0.06:0.001:1:7; the aluminum source is aluminum nitrate; the rare earth source is lanthanum nitrate; the zirconium source is zirconium acetate; the tungsten source is tungsten nitrate; the M source is a nitrate of M; the N source comprises ammonium borate, ammonium silicate and ammonium tellurate.
[0052] The average diameter of the nano-boron fiber is 350nm, and the aspect ratio is 17:1; the auxiliary nanoparticles are a mixture of nano-boron silicon, nano-hafnium nitride, nano-tantalum silicide, and nano-titanium carbide in a mass ratio of 1:0.9:1.2:0.8; the particle size of the auxiliary nanoparticles is 30nm; the binder includes the following components in parts by weight: 4.5 parts of rosin-based hyperbranched epoxy resin, 1.5 parts of hydroxypropyl β-cyclodextrin, and 1.5 parts of (3,6-diaminoacridine-9-yl) boric acid; the rosin-based hyperbranched epoxy resin is made according to the method of Example 1 of the Chinese invention patent with authorization announcement number CN106519188B.
[0053] A method for preparing the ceramic splitting knife comprises the following steps:
[0054] Step S1, mixing the components uniformly by weight to obtain a mixed material, and ball-milling the mixed material to obtain a uniform powder;
[0055] Step S2, drying, sieving, debinding and shaping the uniform powder obtained in step S1 in sequence to obtain a green body;
[0056] Step S3, sintering the green body to obtain a ceramic splitting knife.
[0057] The drying in step S2 is carried out under vacuum, the drying temperature is 83°C, and the drying is carried out to constant weight; the screening in step S2 is through a 400-mesh sieve; the debinding is carried out under a vacuum environment, the debinding temperature is 460°C, and the debinding time is 1.5h; the sintering treatment conditions in step S3 are: heating rate 5°C / min, sintering temperature 1460°C, and insulation time 5h.
[0058] A surface roughening treatment method of the ceramic splitting knife comprises the following steps:
[0059] Step D1, the ceramic splitter is immersed in a mixed acid solution, using a multi-energy field assisted treatment for 18min;
[0060] Step D2, cleaning and drying the ceramic splitting knife processed in step D1 to obtain a roughened ceramic splitting knife product.
[0061] The mixed acid in step D1 is a mixture of nitric acid solution and sulfuric acid solution in a volume ratio of 1:0.9; the mass percentage concentration of the nitric acid solution is 35%, and the mass percentage concentration of the sulfuric acid solution is 55%; the multi-energy field includes ultrasound, microwave and magnetic field; the ultrasound frequency is 70kHz and the power is 250W; the microwave frequency is 2.5GHz and the power is 900W; the magnetic field strength of the magnetic field is 10000Gs.
[0062] Embodiment 3, a ceramic splitting knife is made of the following components in parts by weight: 80 parts of modified alumina powder, 4 parts of nano-boron fiber, 4 parts of auxiliary nanoparticles, and 4 parts of binder; the modified alumina powder is rare earth / Zr / W / M / N co-modified alumina powder; the M is Ga; the N is B, Si, and Te mixed in a molar ratio of 1:1:0.2.
[0063] The preparation method of the modified alumina powder comprises the following steps: placing an aluminum source, a rare earth source, a zirconium source, a tungsten source, an M source, a N source and citric acid in distilled water and stirring evenly, spray drying and calcining in air at 400°C for 3 hours, then calcining in air at 800°C for 9 hours, naturally cooling and grinding the product through a 400-mesh sieve to obtain modified alumina powder; the molar ratio of the aluminum source, the rare earth source, the zirconium source, the tungsten source, the M source, the N source, the citric acid and the distilled water is 1:0.08:0.11:0.04:0.065:0.001:1:8; the aluminum source is aluminum nitrate; the rare earth source is praseodymium nitrate; the zirconium source is zirconium acetate; the tungsten source is tungsten nitrate; the M source is M nitrate; the N source comprises ammonium borate, ammonium silicate and ammonium tellurate.
[0064] The average diameter of the nano-boron fiber is 400nm, and the aspect ratio is 20:1; the auxiliary nanoparticles are a mixture of nano-boron silicon, nano-hafnium nitride, nano-tantalum silicide, and nano-titanium carbide in a mass ratio of 1:1:1.5:0.8; the particle size of the auxiliary nanoparticles is 60nm; the binder includes the following components in parts by weight: 5 parts of rosin-based hyperbranched epoxy resin, 2 parts of hydroxypropyl β-cyclodextrin, and 2 parts of (3,6-diaminoacridine-9-yl) boric acid; the rosin-based hyperbranched epoxy resin is made according to the method of Example 1 of the Chinese invention patent with authorization announcement number CN106519188B.
[0065] A method for preparing the ceramic splitting knife comprises the following steps:
[0066] Step S1, mixing the components uniformly by weight to obtain a mixed material, and ball-milling the mixed material to obtain a uniform powder;
[0067] Step S2, drying, sieving, debinding and shaping the uniform powder obtained in step S1 in sequence to obtain a green body;
[0068] Step S3, sintering the green body to obtain a ceramic splitting knife.
[0069] The drying in step S2 is carried out under vacuum, the drying temperature is 85°C, and the drying is carried out to constant weight; the screening in step S2 is through a 450-mesh sieve; the debinding is carried out under vacuum, the debinding temperature is 470°C, and the debinding time is 2h; the sintering treatment conditions in step S3 are: heating rate 6°C / min, sintering temperature 1520°C, and insulation time 6h.
[0070] A surface roughening treatment method of the ceramic splitting knife comprises the following steps:
[0071] Step D1, the ceramic splitter is immersed in a mixed acid solution, using a multi-energy field assisted treatment for 20min;
[0072] Step D2, cleaning and drying the ceramic splitting knife processed in step D1 to obtain a roughened ceramic splitting knife product.
[0073] The mixed acid in step D1 is a mixture of nitric acid solution and sulfuric acid solution in a volume ratio of 1:1; the mass percentage concentration of the nitric acid solution is 45%, and the mass percentage concentration of the sulfuric acid solution is 65%; the multi-energy field includes ultrasound, microwave and magnetic field; the ultrasound frequency is 70kHz and the power is 300W; the microwave frequency is 2.6GHz and the power is 1100W; the magnetic field strength of the magnetic field is 12000Gs.
[0074] Example 4, a ceramic splitting knife is made of the following components in parts by weight: 85 parts of modified alumina powder, 4.5 parts of nano-boron fiber, 4.5 parts of auxiliary nanoparticles, and 4.5 parts of a binder; the modified alumina powder is a rare earth / Zr / W / M / N co-modified alumina powder; the M is a mixture of Nb, Ni, Ga, Cr, and Co in a molar ratio of 1:1:0.8:2:0.5h; the N is a mixture of B, Si, and Te in a molar ratio of 1:1.1:0.2.
[0075] The preparation method of the modified alumina powder comprises the following steps: placing an aluminum source, a rare earth source, a zirconium source, a tungsten source, an M source, a N source and citric acid in distilled water and stirring evenly, spray drying and calcining in air at 430°C for 3.5 hours, then calcining in air at 850°C for 9.5 hours, naturally cooling and grinding the product through a 450-mesh sieve to obtain the modified alumina powder; the molar ratio of the aluminum source, the rare earth source, the zirconium source, the tungsten source, the M source, the N source, the citric acid and the distilled water is 1:0.08:0.13:0.045:0.075:0.001:1:9.5; the aluminum source is aluminum nitrate; the rare earth source is a mixture of yttrium nitrate, lanthanum nitrate and praseodymium nitrate in a molar ratio of 1:0.8:0.5; the zirconium source is zirconium acetate; the tungsten source is tungsten nitrate; the M source is a nitrate of M; and the N source comprises ammonium borate, ammonium silicate and ammonium tellurate.
[0076] The average diameter of the nano-boron fiber is 450nm, and the aspect ratio is 23:1; the auxiliary nanoparticles are a mixture of nano-boron silicon, nano-hafnium nitride, nano-tantalum silicide, and nano-titanium carbide in a mass ratio of 1:1.1:1.8:0.8; the particle size of the auxiliary nanoparticles is 80nm; the binder includes the following components in parts by weight: 5.5 parts of rosin-based hyperbranched epoxy resin, 2.5 parts of hydroxypropyl β-cyclodextrin, and 2.5 parts of (3,6-diaminoacridine-9-yl) boric acid; the rosin-based hyperbranched epoxy resin is made according to the method of Example 1 of the Chinese invention patent with authorization announcement number CN106519188B.
[0077] A method for preparing the ceramic splitting knife comprises the following steps:
[0078] Step S1, mixing the components uniformly by weight to obtain a mixed material, and ball-milling the mixed material to obtain a uniform powder;
[0079] Step S2, drying, sieving, debinding and shaping the uniform powder obtained in step S1 in sequence to obtain a green body;
[0080] Step S3, sintering the green body to obtain a ceramic splitting knife.
[0081] The drying in step S2 is carried out under vacuum, the drying temperature is 88°C, and the drying is carried out to constant weight; the screening in step S2 is through a 550-mesh sieve; the debinding is carried out under vacuum, the debinding temperature is 500°C, and the debinding time is 2.5h; the sintering treatment conditions in step S3 are: heating rate 7°C / min, sintering temperature 1610°C, and insulation time 7.5h.
[0082] A surface roughening treatment method of the ceramic splitting knife comprises the following steps:
[0083] Step D1, the ceramic splitter is immersed in a mixed acid solution, using a multi-energy field assisted treatment for 23min;
[0084] Step D2, cleaning and drying the ceramic splitting knife processed in step D1 to obtain a roughened ceramic splitting knife product.
[0085] The mixed acid in step D1 is a mixture of nitric acid solution and sulfuric acid solution in a volume ratio of 1:1.1; the mass percentage concentration of the nitric acid solution is 50%, and the mass percentage concentration of the sulfuric acid solution is 80%; the multi-energy field includes ultrasound, microwave and magnetic field; the ultrasound frequency is 90kHz and the power is 350W; the microwave frequency is 2.9GHz and the power is 1300W; the magnetic field strength of the magnetic field is 15000Gs.
[0086] Example 5, a ceramic splitting knife is made of the following components in parts by weight: 90 parts of modified alumina powder, 5 parts of nano-boron fiber, 5 parts of auxiliary nanoparticles, and 5 parts of a binder; the modified alumina powder is a rare earth / Zr / W / M / N co-modified alumina powder; the M is Co; the N is a mixture of B, Si, and Te in a molar ratio of 1:1.2:0.2.
[0087] The preparation method of the modified alumina powder comprises the following steps: placing an aluminum source, a rare earth source, a zirconium source, a tungsten source, an M source, a N source and citric acid in distilled water and stirring evenly, spray drying, calcining in air at 450°C for 4 hours, then calcining in air at 900°C for 10 hours, naturally cooling, grinding the product through a 500-mesh sieve, and obtaining the modified alumina powder; the molar ratio of the aluminum source, the rare earth source, the zirconium source, the tungsten source, the M source, the N source, the citric acid and the distilled water is 1:0.08:0.15:0.05:0.08:0.001:1:10; the aluminum source is aluminum nitrate; the rare earth source is praseodymium nitrate; the zirconium source is zirconium acetate; the tungsten source is tungsten nitrate; the M source is a nitrate of M; and the N source comprises ammonium borate, ammonium silicate and ammonium tellurate.
[0088] The average diameter of the nano-boron fiber is 500nm, and the aspect ratio is 25:1; the auxiliary nanoparticles are a mixture of nano-boron silicon, nano-hafnium nitride, nano-tantalum silicide, and nano-titanium carbide in a mass ratio of 1:1.2:2:0.8; the particle size of the auxiliary nanoparticles is 90nm; the binder includes the following components in parts by weight: 6 parts of rosin-based hyperbranched epoxy resin, 3 parts of hydroxypropyl β-cyclodextrin, and 3 parts of (3,6-diaminoacridine-9-yl) boric acid; the rosin-based hyperbranched epoxy resin is made according to the method of Example 1 of the Chinese invention patent with authorization announcement number CN106519188B.
[0089] A method for preparing the ceramic splitting knife comprises the following steps:
[0090] Step S1, mixing the components uniformly by weight to obtain a mixed material, and ball-milling the mixed material to obtain a uniform powder;
[0091] Step S2, drying, sieving, debinding and shaping the uniform powder obtained in step S1 in sequence to obtain a green body;
[0092] Step S3, sintering the green body to obtain a ceramic splitting knife.
[0093] The drying in step S2 is carried out under vacuum, the drying temperature is 90°C, and the drying is carried out to constant weight; the screening in step S2 is through a 600-mesh sieve; the debinding is carried out under a vacuum environment, the debinding temperature is 510°C, and the debinding time is 3h; the sintering treatment conditions in step S3 are: heating rate 8°C / min, sintering temperature 1660°C, and insulation time 8h.
[0094] A surface roughening treatment method of the ceramic splitting knife comprises the following steps:
[0095] Step D1, the ceramic splitter is immersed in a mixed acid solution, using a multi-energy field assisted treatment for 25min;
[0096] Step D2, cleaning and drying the ceramic splitting knife processed in step D1 to obtain a roughened ceramic splitting knife product.
[0097] The mixed acid in step D1 is a mixture of nitric acid solution and sulfuric acid solution in a volume ratio of 1:1.2; the mass percentage concentration of the nitric acid solution is 55%, and the mass percentage concentration of the sulfuric acid solution is 85%; the multi-energy field includes ultrasound, microwave and magnetic field; the ultrasound frequency is 100kHz and the power is 400W; the microwave frequency is 3.0GHz and the power is 1400W; the magnetic field strength of the magnetic field is 16000Gs.
[0098] Comparative Example 1, a ceramic splitting tool and a surface roughening treatment method thereof, is basically the same as Example 1, except that no M source, (3,6-diaminoacridine-9-yl)boric acid and nano-tantalum silicide are added, and the multi-energy field does not include a magnetic field.
[0099] Comparative Example 2, a ceramic splitting tool and a surface roughening treatment method thereof, is basically the same as Example 1, except that no N source, hafnium nitride and hydroxypropyl β-cyclodextrin are added, and the multi-energy field does not include ultrasound.
[0100] In order to further illustrate the beneficial technical effects of the ceramic splitting knives involved in each embodiment of the present invention, relevant performance tests were conducted on the ceramic splitting knives involved in Examples 1-5 and Comparative Examples 1-2; the test method is as follows:
[0101] (1) Bending strength: 20 ceramic splitting knife samples were taken from each case and the bending strength of the samples was tested using a universal material tester according to the three-point bending method. The test results were averaged.
[0102] (2) Hardness: Two ceramic splitting knife samples were taken from each case. After polishing, the hardness of the samples was tested using a Vickers hardness tester, and the test results were averaged. The hardness is the Vickers hardness measured with a load of 1 kg.
[0103] (3) Apparent porosity: Tested in accordance with GB / T 25995-2010.
[0104] (4) Fracture toughness: Tested according to the three-point bending test in accordance with GB / T 23806-2009.
[0105] (5) Roughness: Use a 3D scanning microscope to observe the sample after surface roughening treatment. Adjust the objective lens magnification to 50 times, find the T surface of the sample under the lens, scan the T surface, and then calculate the roughness of the T surface of the sample (i.e., Ra). Measure 3 points for each sample and take the average value.
[0106]
[0107] As can be seen from Table 1, the ceramic splitters involved in the embodiments of the present invention have better bending strength, hardness and fracture toughness than the comparative products, and have lower apparent porosity. The combined use of M source, (3,6-diaminoacridine-9-yl)boric acid, nano-tantalum silicide, N source, hafnium nitride and hydroxypropyl β-cyclodextrin is beneficial to improving the above properties. Ultrasonic, microwave and magnetic field multi-energy field treatment can improve the surface roughening effect.
[0108] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the contents of the present invention and implement them accordingly. They cannot be used to limit the protection scope of the present invention. All equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A ceramic splitting knife, characterized in that: The invention is made of the following components by weight: 70-90 parts of modified alumina powder, 3-5 parts of nano boron fiber, 3-5 parts of auxiliary nano particles, and 3-5 parts of a binder; the modified alumina powder is rare earth / Zr / W / M / N co-modified alumina powder; the M is at least one of Nb, Ni, Ga, Cr, and Co; the N is a mixture of B, Si, and Te in a molar ratio of 1:(0.8-1.2):0.2; The preparation method of the modified alumina powder comprises the following steps: placing an aluminum source, a rare earth source, a zirconium source, a tungsten source, an M source, an N source and citric acid in distilled water and stirring them evenly, spray drying and calcining them in air at 350-450°C for 2-4 hours, then calcining them in air at 700-900°C for 8-10 hours, and naturally cooling the product and grinding it through a 300-500 mesh sieve to obtain the modified alumina powder; the aluminum source, the rare earth source, the zirconium source, the tungsten source, the M source, the N source and citric acid are placed in distilled water and stirred evenly, spray drying and calcining them in air at 350-450°C for 2-4 hours, then calcining them in air at 700-900°C for 8-10 hours, and then naturally cooling and grinding the product through a 300-500 mesh sieve to obtain the modified alumina powder; The molar ratio of the N source, citric acid and distilled water is 1:0.08:(0.08-0.15):(0.03-0.05):(0.05-0.08):0.001:1:(6-10); the aluminum source is aluminum nitrate; the rare earth source is at least one of yttrium nitrate, lanthanum nitrate and praseodymium nitrate; the zirconium source is zirconium acetate; the tungsten source is tungsten nitrate; the M source is a nitrate of M; the N source includes ammonium borate, ammonium silicate and ammonium tellurate; The auxiliary nanoparticles are a mixture of nano-boron silicon, nano-hafnium nitride, nano-tantalum silicide and nano-titanium carbide in a mass ratio of 1:(0.8-1.2):(1-2):0.8; the particle size of the auxiliary nanoparticles is 10-90nm; and the binder comprises the following components in parts by weight: 4-6 parts of rosin-based hyperbranched epoxy resin, 1-3 parts of hydroxypropyl β-cyclodextrin and 1-3 parts of (3,6-diaminoacridine-9-yl)boric acid.
2. The ceramic splitting knife according to claim 1, characterized in that: The average diameter of the nano boron fiber is 300-500nm, and the aspect ratio is (15-25):
1.
3. A method for preparing the ceramic splitting knife according to any one of claims 1-2, characterized in that: The steps include: Step S1, mixing the components uniformly by weight to obtain a mixed material, and ball-milling the mixed material to obtain a uniform powder; Step S2, drying, sieving, debinding and shaping the uniform powder obtained in step S1 in sequence to obtain a green body; Step S3, sintering the green body to obtain a ceramic splitting knife.
4. The method for preparing the ceramic splitting knife according to claim 3, characterized in that: The drying in step S2 is carried out under vacuum, the drying temperature is 80-90°C, and the drying is carried out to constant weight; the screening in step S2 is through a 300-600 mesh sieve; the debinding is carried out under a vacuum environment, the debinding temperature is 440-510°C, and the debinding time is 1-3h; the sintering treatment conditions in step S3 are: heating rate 3-8°C / min, sintering temperature 1430-1660°C, and insulation time 4-8h.
5. A surface roughening treatment method for a ceramic splitting knife according to any one of claims 1 to 2, characterized in that: The steps include: Step D1, immersing the ceramic splitting knife in a mixed acid solution, and using a multi-energy field to assist treatment for 15-25 minutes; the mixed acid is a mixture of a nitric acid solution and a sulfuric acid solution in a volume ratio of 1: (0.8-1.2); the mass percentage concentration of the nitric acid solution is 25-55%, and the mass percentage concentration of the sulfuric acid solution is 45-85%; the multi-energy field includes ultrasound, microwave and magnetic field; the ultrasound frequency is 50-100kHz, and the power is 200-400W; the microwave frequency is 2.3-3.0GHz, and the power is 700-1400W; the magnetic field strength of the magnetic field is 8000-16000Gs; Step D2, cleaning and drying the ceramic splitting knife processed in step D1 to obtain a roughened ceramic splitting knife product.
